Possíveis contribuições do xadrez na educação física escolar : uma experiência pedagógica nos anos finais do ensino fundamental - Soares, Adriana Ferreira (2023)
The research focuses on exploring the incorporation of chess into physical education classes through planned activities that aim to promote student protagonism in their formative journey. Currently, schools, as educational institutions, and physical education, as a curricular component, aim to develop individuals with critical thinking abilities who can act autonomously and become protagonists in their own reality. Therefore, the objective of this study is to understand the contributions of chess to the development of autonomy and protagonism among 7th-grade students in a public school in São José do Rio Claro, Mato Grosso, Brazil. Recognizing that chess, as a sporting practice, is an important pedagogical tool that can significantly influence the formation of critical, autonomous, and inclusive individuals, promoting inclusion and socialization. The research methodology chosen is a qualitative ethnographic approach, specifically ethnography of school practice. The data collection instruments utilized were questionnaires with open-ended and closed questions, as well as field/lesson diaries. The data was collected in three stages. The first stage involved administering an entry questionnaire to the 7th-grade class to assess the students' prior knowledge of chess and identify actions/attitudes of autonomy and protagonism associated with this knowledge. The second stage commenced with the implementation of the didactic unit with the class, during which the researching teacher observed and recorded in the field diary the challenges and progress perceived in terms of the contribution of chess teaching and learning to the development of student autonomy and protagonism. Finally, in the third stage, an exit questionnaire was administered at the end of the didactic unit to identify and evaluate the outcomes of the intervention. The data analysis included transcriptions of the questionnaires answered by the students and analysis of the field diary. The primary results indicated that chess facilitated the development of autonomy and student protagonism by stimulating strategic decision-making and independent problemsolving. The students reported feeling more confident and capable of facing challenges not only in chess but also in other areas of their lives. These findings reinforce the importance of chess as a pedagogical tool for the formation of autonomous and critical individuals, as well as a means to stimulate student protagonism through chess teaching and learning.